Microvascular reactivity is altered early in patients with acute respiratory distress syndrome - Orbegozo Cortés, Diego (Respir Res, 2016)
BACKGROUND: Acute respiratory distress syndrome (ARDS) is associated with vascular endothelial dysfunction. The resultant microvascular reactivity can be assessed non-invasively using near-infrared spectroscopy (NIRS) and a vascular occlusion test (VOT) and changes have been correlated with severity of organ dysfunction and mortality in other critically ill populations. We used NIRS to study the presence of microcirculatory alterations in patients with ARDS. METHODS: We studied 27 healthy volunteers and 32 ARDS patients admitted to our intensive care department. NIRS measurements were performed within 24 h after diagnosis (Berlin definition). VOTs were performed by inflating an arm-cuff to a pressure greater than the systolic pressure for 3 min, followed by rapid deflation. The descending (Desc) and ascending (Asc) thenar muscle oxygen saturation (StO(2)) slopes were calculated. We compared data from volunteers with those from ARDS patients, from ARDS survivors and non-survivors, and from ARDS survivors who required <7 days ventilatory support (good evolution) with those who required >7 days support or died (poor evolution). RESULTS: ARDS patients had lower StO(2) values [75(67–80) vs 79(76–81) %, p = 0.04] and Asc slopes [185(115–233) vs 258(216–306) %/min, p < 0.01] than healthy volunteers, but Desc slopes were similar. The Asc slope was lower in the patients with a poor evolution than in the other patients [121(90–209) vs 222(170–293) %/min, p < 0.01], and in the non-survivors than in the survivors [95(73–120) vs 212(165–252) %/min, p < 0.01]. CONCLUSIONS: In ARDS patients, microvascular reactivity is altered early, and the changes are directly related to the severity of the disease. The ascending slope is the best determinant of outcome. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12931-016-0375-y) contains supplementary material, which is available to authorized users.